Analisis Media Permainan Puzzle Untuk Menunjang Literasi Penyandang Disabilitas Tunarungu Di TPQLB Spirit Dakwah Indonesia - Putri, Windy Silviana; Prajawinanti, Arin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
Learning media is a medium that can be used by teachers to convey a message and can stimulate the mind, increase the enthusiasm, attention, and willingness of students so that they can motivate students in the learning process. One of the Learning media is a puzzle game. The puzzle game is used by TPQLB Spirit Dakwah Indonesia to support literacy for students with hearing impairments. The method used is descriptive qualitative. The sample in this study consisted of 9 informants consisting of 3 students with hearing impairments, 3 permanent teachers. 3 guardians of the students who were the guardians of the students who were used as informants. Data collection techniques use observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman models, namely data reduction, data disply, and conclusion drawing/verification. The results of this study indicate that students with hearing impairments can be said to be literate. It can be seen that deaf students are able to write and read. Reading literacy includes reading volumes and asmaul husna. Writing literacy includes writing hijaiyah letters, writing Arabic numerals, writing calligraphy, writing fiqh material such as procedures for prayer and procedures for ablution.